2016
DOI: 10.5370/jeet.2016.11.5.1137
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Control of DFIG for Wind Energy Conversion System Using Feedback Linearization

Abstract: -This paper presents a dynamic modeling and control of doubly fed induction-generator (DFIG) based variable speed wind-turbine. The dynamic model of DFIG is incorporated with all system components which provide simple design and controls. The penetration of wind power is increasing into electrical networks, which necessitates more comprehensive studies to recognize the interaction between the wind farms and the power grid. This paper presents the dynamic model of a DFIG based wind turbine connected to the grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These variable-speed wind plants are decoupled from the corresponding electricity grid by power electronic converters. Different from synchronous generators, some types of wind plants are not able to play a part in frequency control activities such as inertia and governor response after a disturbance [33][34][35][36][37]. Although several control methodologies have been developed to allow Type-3 and Type-4 wind plants to be used for frequency regulation [38,39], such solutions are still not mandatory and normally do not operate for the Type-3 wind plant.…”
Section: Vulnerability Of the Modern Grid As A Results Of High Penetramentioning
confidence: 99%
“…These variable-speed wind plants are decoupled from the corresponding electricity grid by power electronic converters. Different from synchronous generators, some types of wind plants are not able to play a part in frequency control activities such as inertia and governor response after a disturbance [33][34][35][36][37]. Although several control methodologies have been developed to allow Type-3 and Type-4 wind plants to be used for frequency regulation [38,39], such solutions are still not mandatory and normally do not operate for the Type-3 wind plant.…”
Section: Vulnerability Of the Modern Grid As A Results Of High Penetramentioning
confidence: 99%
“…A wind turbine operates on a particular site according to the design parameters, cut-in wind speed, cut-out wind speed and rated power are selected according to the location of wind characteristics. Wind turbine efficiency is not dependent upon the characteristics of wind site but on wind speed distribution [49], [52]. It is found that the maximum efficiency of a wind turbine is 59 %.…”
Section: Power Generation With Various Windturbinesmentioning
confidence: 99%
“…Wind power plant installed capacity is 4.9 MW with generation from wind 146 GW per year. NEPRA has regulated tariff rate of 16.109 cents/kW h for FFC Energy Ltd [52]- [54]. It has completed 50 megawatt wind farm in record time by FFC Energy Limited (FFCEL), a subsidiary of FFC well-known by a dream to commence and encourage renewable energy and environmentally friendly plants in Pakistan.…”
Section: A Fauji Fertilizer Company (Ffc) Projectmentioning
confidence: 99%
“…When the rotor speed is closer to the synchronous frequency, the system possesses a higher bandwidth for feedback stator flux. Multiple-input and multiple-output (MIMO) system of state feedback linearization control is described in [38][39][40][41][42]. However, the foremost intention of feedback linearization is to transform nonlinear models into linear ones and it is the most authentic approach for handling practical nonlinear control designs.…”
Section: 1mathematical Modeling Of Proposed Control Schemementioning
confidence: 99%